"Not Fair, Not Fun, Not Safe": Confronting Alienation in Physical Education Class. (4th March 2022) - Kim, Mijoo
Abstract: When students feel alienated, they develop various avoidance strategies, such as becoming spectators, blending into the background, faking participation, pretending to be sick or have an injury, or simply not attending class. Consequently, students lose out on opportunities to improve their skills and interact with others, which alienates them further. This paper addresses this concern by looking closely at alienation and students' avoidance strategies so that physical educators can disrupt alienation to promote greater PA engagement.